A Future Forecasting for FMCG Firm Performance in Covid-19: An Investigation of Consumer and Business Survival - Sun, Yunpeng; Li, Ying; Wang, Yujing; Jiang, Dayang; Liu, Xiaojun (Frontiers in Public Health, 2021)
The Covid-19 outbreak has spread over the world, limiting population and trade, causing job losses, and forcing businesses to close. The study's goal is to look at Covid-19's pandemic and consumer survival as a mediator for the future of running a business when FMCG companies are doing well. The researchers employed a basic random sampling strategy to do a layered transverse evaluation of samples. EFA, CFA, and SEM are used to choose data collection techniques for participants at Covid-19. According to the data, Malaysia has resulted in job losses, business growth, and customer satisfaction retention, as well as an increase in unemployment, company closures, and a drop in overall GDP. The impact of the Covid-19 epidemic on survival, production, and GDP has been demonstrated. Incorporating technology into all aspects of a company's working practices reveals the necessity and capacity of the organization to adapt to new scenarios.